Fire extinguishment using a 4 m long flying-hose-type robot with multiple water-jet nozzles. (2nd June 2020) - Ando, Hisato; Ambe, Yuichi; Yamaguchi, Tomoka; Yamauchi, Yu; Konyo, Masashi; Tadakuma, Kenjiro; Maruyama, Shigenao; Tadokoro, Satoshi
Abstract : Several ground-based robots have been developed to support dangerous fire extinguishing activities; however, in such cases, it is difficult to access the fire sources directly. The concept of a hose-type robot called 'dragon firefighter' (DFF) is proposed herein; it emits high-pressure water from a fire hose and floats it for direct transmission to the fire point. A stable levitation with 2 m length was realized; however, for practical use, we must extend the floating length of the robot. This study was aimed at extending the floating length of a hose-like body. Two primary issues need to be addressed for achieving this aim: lack of a sufficient reaction force for flying and torsion along the longitudinal direction of the body. Therefore, our robot was first extended using a middle nozzle. A flow channel model was constructed, and an injection hole was designed to achieve a cross-sectional area that could generate a sufficient reaction force. An adjustable jet direction nozzle was designed with four degrees of freedom to control the net force and torsion torque. Finally, a simple proportional-derivative control was incorporated to adjust the twist angle, float the DFF (3.6 m length), surmount a wall, and subsequently, extinguish the fire. GRAPHICAL ABSTRACT: UF0001